MENUMBUHKAN MINAT BACA ANAK USIA DINI MELALUI BIMBINGAN BELAJAR - ridha Ayu Wintari; Muchammad Saiful Machfud (AflahConsilia : Jurnal Bimbingan dan Konseling, 2022)
Indonesia is known as one of the countries with the lowerst interest in reading. To overcome this problem, it is necessary to grow in reading in the nation’schildren from an early age. Early childhood has a period called the golden age, where the growth and development of children is very fast. In order to optimize the potential of children, learning guidence is needed especially in growing children’s interest in reading. The method used in ibi’s research is in the from of library research. Data collection is done through research that has been published in the last 5 years. Descriptiv eanalysis method isused to describe in the form of a descriptive narrative that is broader and comprehensove. The results of the study show that tutoring in fostering interest in reading for early childhood can be carried out individually and in groups, both formally and non-formally. Things that need to be considered in fostering interest in early childhood reading is the material provided must be relevant to the child’ sage. So that it can foster a sense of pleasure and love in reading and not cause boredom which results in laziness to read in children.